Effect of street network design on traffic congestion and traffic safety. (October 2021) - Choi, Dong-ah; Ewing, Reid
Abstract: We examine the effects of street network design on congestion levels and crash rates in neighborhoods across Utah's Wasatch Front. We employ propensity score matching to select pairwise neighborhood samples that have other similar characteristics but differ greatly in street network design. Our results show that denser and more connected neighborhoods have significantly lower congestion levels, but they do not have measurably lower (or higher) crash rates, presumably due to the prevalence of four-way intersections. This study can help guide data-driven decision making on street network design standards for many of the growing urban areas across the country and globe. Highlights: The effects of neighborhood street network design on congestion levels and crash rates were examined. Propensity score matching was used to select pairwise neighborhood samples that differ greatly in street network design. The research found denser and more connected neighborhoods associated with lower congestion levels. However, denser and more connected network designs were not significantly related to crash rates.